2016
DOI: 10.1007/s10528-016-9773-6
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Exosomes as Biomarkers for Evaluating and Monitoring Critically Ill Polytrauma Patients with Sepsis

Abstract: Regarding genetic biomarkers for early assessment and monitoring the clinical course in polytrauma patients with sepsis, in recent years a remarkable evolution has been highlighted. One of the main representatives is the exosome miRNAs. In this paper, we would like to present in more details the various methods of using exosome miRNAs as a biomarker for monitoring polytrauma patients with sepsis, as well as establishing a belated outcome by aggregating the entire clinical aspects. The use of exosome miRNAs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Zhao et al also found that the serum levels of miR-150 decreased in a rat sepsis model, providing a valuable tool in evaluating the prognosis of sepsis ( 11 ). Similarly, the expression of miR-150 was reported to be decreased in a patient with sepsis ( 46 ). A previous study found that MLCK , including MYLK1, MYLK2 and MYLK3 , may not upregulate endothelial permeability induced by LPS exposure, whereas hyper-permeability was observed in sepsis and other inflammatory situations ( 47 ).…”
Section: Discussionmentioning
confidence: 95%
“…Zhao et al also found that the serum levels of miR-150 decreased in a rat sepsis model, providing a valuable tool in evaluating the prognosis of sepsis ( 11 ). Similarly, the expression of miR-150 was reported to be decreased in a patient with sepsis ( 46 ). A previous study found that MLCK , including MYLK1, MYLK2 and MYLK3 , may not upregulate endothelial permeability induced by LPS exposure, whereas hyper-permeability was observed in sepsis and other inflammatory situations ( 47 ).…”
Section: Discussionmentioning
confidence: 95%
“…This reaction takes place only if it is catalyzed by the DiGeorge Syndrome Critical Region 8 (DGCR8). [43][44][45][46] The transporting protein, Exportin 5, will then act on the pre-miRNAs, which will transfer the epigenetic complex from the nucleus to the cell cytoplasm. [47][48][49] Once the signal that the complex has reached the cytoplasm is received, RNA polymerase III (Dicer) and trans-activator RNA binding protein (TRBP) attack it and lead to the formation of mature miRNAs.…”
Section: The Most Common Molecular Mechanisms Involved In Cvdsmentioning
confidence: 99%
“…From a molecular point of view, microRNAs are synthesized in the cell nucleus through the action of RNA polymerase II on certain specific genes. Hence, the initial species, the pri-microRNAs, are formed following complex reactions [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. In the next step, RNAse III endonuclease, also called Drosha, activates the pri-microRNAs.…”
Section: Biochemical and Biosynthesis Aspects Of Micrornasmentioning
confidence: 99%
“…A series of complex mechanisms involved in the pathophysiology and biochemistry of sepsis have been studied for the past several years. However, the critically ill polytrauma patient is so complex biochemically and molecularly that no specific biochemical pathways have been found in which intervention could increase survival rates, or decrease the incidence of sepsis and multiple organ dysfunction syndrome (MODS) [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. However, in the last few years, a series of microRNA epigenetic species have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation